IMPACT OF SOME OVERSEAS MONETARY VARIABLES ON INDONESIA: SVAR APPROACH - Subagyo, Ahmad; Witjaksono, Armanto (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2017)
This study aims to investigate how the influence of monetary variables from abroad to Indonesia’s monetary conditions. This study uses exchange rate variables, interest rates of U.S. central banks, world oil prices and interest rates of Indonesian banks. This study proposes a short-term SVAR analysis using FEVD and IRF as an additional analysis tool. From the research done in the explanation that with SVAR model that in the proposal is less precise, the result for IRF and FEVD analysis can not be made as additional material of analysis tool from SVAR model which in proposal.